Complexation mechanism of olefin with silver ions dissolved in a polymer matrix and its effect on facilitated olefin transport - Kim, JH; Min, BR; Won, J; Kang, YS (WILEY-V C H VERLAG GMBH, 2002)
Remarkable separation performance of olefin/paraffin mixtures was previously reported by facilitated olefin transport through silver-based polymer electrolyte membranes. The mechanism of facilitated olefin transport in solid membranes of AgCF3SO3 dissolved in poly(N-vinyl pyrrolidone) (PVP) is investigated. In silver polymer electrolyte membranes, only free anions are present up to the 2:1 mole ratio of [C=O]:[Ag], and ion pairs start to form at a ratio of 1:1, followed by higher-order ionic aggregates above a ratio of 1:2. At silver concentrations above 3:1, the propylene permeance increases almost linearly with the total silver concentration, unexpectedly, regardless of the silver ionic constituents. It was also found that all the silver constituents, including ion pairs and higher order ionic aggregates, were completely redissolved into free anions under the propylene environment; this suggests that propylene can be a good ligand for the silver cation. From these experimental findings, a new mechanism for the complexation reaction between propylenes and silver salts in silver-polymer electrolytes was proposed. The new mechanism is consistent with the linearity between the propylene permeance and the total silver concentration regardless of the kind of the silver constituents. Therefore, the facilitated propylene transport through silver-polymer electrolytes may be associated mainly with the silver cation weakly coordinated with both carbonyl oxygen atoms and propylene.
Keywords: RAMAN; ELECTROLYTES; MEMBRANES; SALTS